Social Anxiety as a Consequence of Non-consensually Disseminated Sexually Explicit Media Victimization - Campbell, Julia K. (Journal of interpersonal violence, 2022)
The purpose of this qualitative study was to explore consequences of the non-consensual dissemination of sexually explicit media (NCDSEM) for survivors, with an emphasis on how NCDSEM may impact social relationships and social anxiety. One-on-one telephone interviews with (N = 17) self-identified survivors of NCDSEM were conducted between May and December 2019. Interviews were analyzed using a flexible coding methodology. There were five main ways in which participants described consequences of NCDSEM: (a) fear of going out in public, (b) fear of engaging in relationships, (c) fear of applying to jobs, (d) fear of seeking help, and (e) influencing depression and feelings of anxiety. These findings suggest that, for some people, NCDSEM victimization may influence whether and how they subsequently socialize with other people.